Polymicrogyria is Associated With Pathogenic Variants in PTEN. - Shao, Diane D; Achkar, Christelle M; Lai, Abbe; Srivastava, Siddharth; Doan, Ryan N; Rodan, Lance H; Chen, Allen Y; Poduri, Annapurna; Yang, Edward; Walsh, Christopher A (Ann Neurol, 2020)
OBJECTIVE: Congenital structural brain malformations have been described in patients with pathogenic phosphatase and tensin homologue (PTEN) variants, but the frequency of cortical malformations in patients with PTEN variants and their impact on clinical phenotype are not well understood. Our goal was to systematically characterize brain malformations in patients with PTEN variants and assess the relevance of their brain malformations to clinical presentation. METHODS: We systematically searched a local radiology database for patients with PTEN variants who had available brain magnetic resonance imaging (MRI). The MRI scans were reviewed systematically for cortical abnormalities. We reviewed electroencephalogram (EEG) data and evaluated the electronic medical record for evidence of epilepsy and developmental delay. RESULTS: In total, we identified 22 patients with PTEN pathogenic variants for which brain MRIs were available (age range 0.4-17 years). Twelve among these 22 patients (54%) had polymicrogyria (PMG). Variants associated with PMG or atypical gyration encoded regions of the phosphatase or C2 domains of PTEN. Interestingly, epilepsy was present in only 2 of the 12 patients with PMG. We found a trend toward higher rates of global developmental delay (GDD), intellectual disability (ID), and motor delay in individuals with cortical abnormalities, although cohort size limited statistical significance. INTERPRETATION: Malformations of cortical development, PMG in particular, represent an under-recognized phenotype associated with PTEN pathogenic variants and may have an association with cognitive and motor delays. Epilepsy was infrequent compared to the previously reported high risk of epilepsy in patients with PMG. ANN NEUROL 2020;88:1153-1164.
Keywords: Adolescent; Brain; Child; Child, Preschool; Comorbidity; Databases, Genetic; Developmental Disabilities; Electroencephalography; Female; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Massachusetts; Neuroimaging; Polymicrogyria; PTEN Phosphohydrolase

Posterior Neocortex-Specific Regulation of Neuronal Migration by CEP85L Identifies Maternal Centriole-Dependent Activation of CDK5. - Kodani, Andrew; Kenny, Connor; Lai, Abbe; Gonzalez, Dilenny M; Stronge, Edward; Sejourne, Gabrielle M; Isacco, Laura; Partlow, Jennifer N; O'Donnell, Anne; McWalter, Kirsty; Byrne, Alicia B; Barkovich, A James; et al. (Neuron, 2020)
Genes mutated in human neuronal migration disorders encode tubulin proteins and a variety of tubulin-binding and -regulating proteins, but it is very poorly understood how these proteins function together to coordinate migration. Additionally, the way in which regional differences in neocortical migration are controlled is completely unknown. Here we describe a new syndrome with remarkably region-specific effects on neuronal migration in the posterior cortex, reflecting de novo variants in CEP85L. We show that CEP85L is required cell autonomously in vivo and in vitro for migration, that it localizes to the maternal centriole, and that it forms a complex with many other proteins required for migration, including CDK5, LIS1, NDE1, KIF2A, and DYNC1H1. Loss of CEP85L disrupts CDK5 localization and activation, leading to centrosome disorganization and disrupted microtubule cytoskeleton organization. Together, our findings suggest that CEP85L highlights a complex that controls CDK5 activity to promote neuronal migration.
Keywords: Cell Movement; Centrioles; Child; Child, Preschool; Cyclin-Dependent Kinase 5; Cytoskeletal Proteins; Female; Humans; Lissencephaly; Male; Microtubules; Neocortex; Nerve Tissue Proteins; Neurons; Oncogene Proteins, Fusion; Young Adult

Homozygous Missense Variants in NTNG2, Encoding a Presynaptic Netrin-G2 Adhesion Protein, Lead to a Distinct Neurodevelopmental Disorder. - Dias, Caroline M; Punetha, Jaya; Zheng, Céline; Mazaheri, Neda; Rad, Abolfazl; Efthymiou, Stephanie; Petersen, Andrea; Dehghani, Mohammadreza; Pehlivan, Davut; Partlow, Jennifer N; Posey, Jennifer E; Salpietro, Vincenzo; et al. (Am J Hum Genet, 2019)
NTNG2 encodes netrin-G2, a membrane-anchored protein implicated in the molecular organization of neuronal circuitry and synaptic organization and diversification in vertebrates. In this study, through a combination of exome sequencing and autozygosity mapping, we have identified 16 individuals (from seven unrelated families) with ultra-rare homozygous missense variants in NTNG2; these individuals present with shared features of a neurodevelopmental disorder consisting of global developmental delay, severe to profound intellectual disability, muscle weakness and abnormal tone, autistic features, behavioral abnormalities, and variable dysmorphisms. The variants disrupt highly conserved residues across the protein. Functional experiments, including in silico analysis of the protein structure, in vitro assessment of cell surface expression, and in vitro knockdown, revealed potential mechanisms of pathogenicity of the variants, including loss of protein function and decreased neurite outgrowth. Our data indicate that appropriate expression of NTNG2 plays an important role in neurotypical development.

Somatic SLC35A2 variants in the brain are associated with intractable neocortical epilepsy. - Winawer, Melodie R; Griffin, Nicole G; Samanamud, Jorge; Baugh, Evan H; Rathakrishnan, Dinesh; Ramalingam, Senthilmurugan; Zagzag, David; Schevon, Catherine A; Dugan, Patricia; Hegde, Manu; Sheth, Sameer A; McKhann, Guy M; et al. (Ann Neurol, 2018)
OBJECTIVE: Somatic variants are a recognized cause of epilepsy-associated focal malformations of cortical development (MCD). We hypothesized that somatic variants may underlie a wider range of focal epilepsy, including nonlesional focal epilepsy (NLFE). Through genetic analysis of brain tissue, we evaluated the role of somatic variation in focal epilepsy with and without MCD. METHODS: We identified somatic variants through high-depth exome and ultra-high-depth candidate gene sequencing of DNA from epilepsy surgery specimens and leukocytes from 18 individuals with NLFE and 38 with focal MCD. RESULTS: We observed somatic variants in 5 cases in SLC35A2, a gene associated with glycosylation defects and rare X-linked epileptic encephalopathies. Nonsynonymous variants in SLC35A2 were detected in resected brain, and absent from leukocytes, in 3 of 18 individuals (17%) with NLFE, 1 female and 2 males, with variant allele frequencies (VAFs) in brain-derived DNA of 2 to 14%. Pathologic evaluation revealed focal cortical dysplasia type Ia (FCD1a) in 2 of the 3 NLFE cases. In the MCD cohort, nonsynonymous variants in SCL35A2 were detected in the brains of 2 males with intractable epilepsy, developmental delay, and magnetic resonance imaging suggesting FCD, with VAFs of 19 to 53%; Evidence for FCD was not observed in either brain tissue specimen. INTERPRETATION: We report somatic variants in SLC35A2 as an explanation for a substantial fraction of NLFE, a largely unexplained condition, as well as focal MCD, previously shown to result from somatic mutation but until now only in PI3K-AKT-mTOR pathway genes. Collectively, our findings suggest a larger role than previously recognized for glycosylation defects in the intractable epilepsies. Ann Neurol 2018.